Can The Use Of QR Codes Enhance M-Learning In A Blended Learning Environment? - Latifah Abdol Latif; Mansor Fadzil; Tengku Amina Munira Tengku Mohd Azzman Shariffadeen; Ng, Man San (2011)

(untitled)
In recent years, with the introduction of smartphones, tablet computers and the advancement of information and communication technology (ICT), there has been a growing interest in the use of Quick Response (QR) codes for educational purposes. The majority of scholarly accounts in this particular topic have been those related to managing libraries, and to a lesser extent to teaching and learning. At present, applications of QR codes in higher education are minimal, and even fewer in a blended learning environment. This paper describes an exploratory project that attempts to introduce three specific examples of basic QR code-driven activities in an Open and Distance Learning (ODL) institution. Learners were asked to scan QR codes using mobile smartphones or tablet computers. Three different types of content, i.e. text-based instruction, Uniform Resource Locater (URL) of video lectures (called iLectures) and URL of self-test activities were made available to learners via the QR codes. A cross-sectional survey was carried out on learners who have been introduced to the QR codes. The objectives of this project are multi-pronged: first is to create awareness of QR codes among learners; second is to encourage and push the use of specific online materials via mobile devices; and third is to determine learners’ attitudes/perceptions towards the use of a combination of smartphones and QR codes in learning. This study is important to an ODL institution like Open University Malaysia (OUM). For a provider of flexible delivery of instructional materials, QR codes can play a significant role in enhancing mobile learning (or m-learning) and engaging learners in their learning process. The research findings are expected to indicate whether or not the integration of smartphones and QR codes can be considered an effective way forward in achieving a semi-ubiquitous m-learning environment. (Abstract by authors)